Impact of ICT in the Tourism Sector: Ecuadorian Case. - Rodriguez, M L; Pazmiño, M F; López, OA; Gómez, JM; Mendoza, LA; Arteaga, MM; Martínez, AA; Iza, CL (International Journal of Membrane Science and Technology, 2023)
The rapid development of Information and Communication Technologies (ICT) has profoundly impacted international tourism. This research analyzes the utilization of ICTs in the Ecuadorian tourism sector, specifically within micro, small, and medium-sized enterprises (MSMEs). The study employs an exploratory, descriptive, and bibliographic methodology, including a questionnaire distributed to 378 tourism experts representing Ecuadorian tourism MSMEs. The objective is to examine the relationship between ICTs and current tourism practices. The findings demonstrate that ICTs support 80% of MSME activities in the Ecuadorian tourism sector. They also provide benefits such as improved access to information about Ecuadorian tourist sites, enhanced communication between companies and tourists, and increased ease of tourist mobility.